Measurement of electrons from beauty hadron decays in pp collisions at √s=7 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Constantin, Paul; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Koch, Kathrin; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; et al. (Physics letters, 2013)
The production cross section of electrons from semileptonic decays of beauty hadrons was measured at mid-rapidity (|y|<0.8) in the transverse momentum range 1<pT<8 GeV/c with the ALICE experiment at the CERN LHC in pp collisions at a center of mass energy s=7 TeV using an integrated luminosity of 2.2 nb−1. Electrons from beauty hadron decays were selected based on the displacement of the decay vertex from the collision vertex. A perturbative QCD calculation agrees with the measurement within uncertainties. The data were extrapolated to the full phase space to determine the total cross section for the production of beauty quark-antiquark pairs.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" in sNN tiefgestellt
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, P. Constantin, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, K. Koch, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J.H. Stiller, S. Vallero, Y. Wang, B. Windelband, A. Zimmermann und weitere 959
Gesehen am 30.04.2021